Immunomodulation induced by central nervous system-related peptides as a therapeutic strategy for neurodegenerative disorders - Palumbo, María Laura (2021)
Fil: Palumbo, María Laura. Universidad Nacional de San Antonio de Areco. Universidad Nacional del Noroeste de la Provincia.de Buenos Aires. Centro de Investigaciones y Transferencia del Noroeste de la Provincia de Buenos Aires. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina